The application of modelling tasks in the classroom – why and how? with reflections on an EU teacher training course - Ambrus, Gabriella; Vancsó, Ödön; Koren, Balázs (Teaching Mathematics and Computer Science, 2012)
The aim of the article is to present the concept of mathematical modelling in the classroom. LEMA (Learning and Education in and through Modelling and Applications) was an EU Comenius funded project in which mathematics educators from six countries worked to produce materials to support teachers’ professional development. A group of voluntary Hungarian mathematics teachers were taught modelling for a year and we were and still are given feedback continously. The article leads us from the general concept of mathematical modelling to its practice in the classroom. It presents difficulties that teachers have to face when doing modelling lessons and their students’ reactions are also mentioned. We present sample tasks from the material of the teacher training course as well as tasks that were created by the participants.